2005
DOI: 10.1002/mc.20073
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and protein expression of the DNA mismatch repair gene,hMLH1, of lung cancer in chromate-exposed workers

Abstract: Our previous studies of lung cancer in chromate-exposed workers (chromate lung cancer) have revealed that the frequency of replication error (RER) in chromate lung cancer is very high. We examined whether the RER phenotype of chromate lung cancer is due to an abnormality of DNA mismatch repair protein. We investigated the expression of a DNA mismatch repair gene, hMLH1, and hMSH2 proteins using immunohistochemistry and microsatellite instability (MSI) in 35 chromate lung cancers and 26 nonchromate lung cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 21 publications
5
89
0
1
Order By: Relevance
“…In fact exposure to environmental toxicants/ carcinogens, particularly heavy metals, is correlated with microsatellite instability in adult cancers due to occupational exposure. 33,34 In our hepatoblastoma series the high-and low-level microsatellite instability phenotypes did not appear to be specifically associated with b-catenin alterations, p53 mutations, and epithelial vs epithelial/mesenchymal histology. A role of preoperative chemotherapy in determining the observed genetic alterations is unlikely, as mutations and microsatellite instability were found in both preoperatively-treated and -untreated hepatoblastoma cases.…”
Section: Discussionmentioning
confidence: 70%
“…In fact exposure to environmental toxicants/ carcinogens, particularly heavy metals, is correlated with microsatellite instability in adult cancers due to occupational exposure. 33,34 In our hepatoblastoma series the high-and low-level microsatellite instability phenotypes did not appear to be specifically associated with b-catenin alterations, p53 mutations, and epithelial vs epithelial/mesenchymal histology. A role of preoperative chemotherapy in determining the observed genetic alterations is unlikely, as mutations and microsatellite instability were found in both preoperatively-treated and -untreated hepatoblastoma cases.…”
Section: Discussionmentioning
confidence: 70%
“…In a previous study from Korea, the variation À93 G>A within MLH1 was found associated with increased risk of squamous cell lung carcinoma (42). Moreover, the exposure to chromate seems to promote lung cancer also through the inhibition of hMLH1 (43). Finally, engineered mice deficient in the MMR gene Mutyh are prone to develop lung cancer (44).…”
Section: Discussionmentioning
confidence: 92%
“…Prenatal methylmercury exposure increases the level of H3K27me3 and decreases the level of H3Ac their promoters. 18,82 Furthermore, DNA hypermethylation in the promoter regions of the Adenomatous Polyposis Coli (APC) tumor suppressor and MGMT is detected in these samples, although a correlation with their gene expression levels is not established. 16 Chromium has also been found to induce DNA hypermethylation of the gpt promoter and subsequent silencing of its expression in cells.…”
Section: Mercurymentioning
confidence: 99%